Letter to the Editor Regarding the “Effectiveness of 190 μg Fluocinolone Acetonide and 700 μg Dexamethasone Intravitreal Implants in Diabetic Macular Edema Using the Area-Under-the-Curve Method: The Constant Analysis” Article [Letter] - Taylor K (Dove Medical Press, 2020)
Kasserine Taylor,1 Michael W Stewart2 1Department of Ophthalmology, Mayo Clinic Florida, Jacksonville, FL, USA; 2Cornell University, Ithaca, NY, USACorrespondence: Michael W StewartDepartment of Ophthalmology, Mayo Clinic Florida, 4500 San Pablo Road, Jacksonville, FL 32250, USATel +1 904-953-2232Fax +1 904-953-7040Email stewart.michael@mayo.edu In a recent edition of Clinical Ophthalmology, Zarranz-Ventura and Mali presented1 an area-under-the-curve (AUC) analysis that directly compared the best corrected visual acuity (BCVA) improvements in the  pivotal diabetic macular edema (DME) trials (FAME and MEAD) for the fluocinolone acetonide implant (Iluvien) and the dexamethasone implant (Ozurdex). They concluded that patients in FAME had superior BCVA improvement over the course of 36 months. We contend that this analysis and the resultant conclusions are flawed because of methodologic deficiencies in the MEAD trial.   View the original paper by Zarranz-Ventura and Mali